Sputum from chronic obstructive pulmonary disease patients inhibits T cell migration in a microfluidic device. Issue 1 (19th March 2019) - Ren, Xiaoou; Wu, Jiandong; Levin, David; Santos, Susy; de Faria, Ricardo Lobato; Zhang, Michael; Lin, Francis
Abstract: Chronic obstructive pulmonary disease (COPD) is a common lung disease characterized by narrowed airways, resulting in serious breathing difficulty. Previous studies have demonstrated that inflammatory infiltration of leukocytes in the airway is associated with the pathogenesis of COPD. In the present study, we employed a microfluidic approach to assess the effect of COPD sputum on activated human peripheral blood T cell migration and chemotaxis under well‐controlled gradient conditions. Our results showed considerable basal migration of T cells derived from peripheral blood of COPD patients and healthy controls in the medium control groups. By contrast, the migration of T cells from COPD patients and healthy controls was significantly inhibited in the presence of a gradient of sputum supernatant from COPD patients. Furthermore, chemotaxis of T cells from COPD patients or healthy subjects toward an SDF‐1α gradient was clearly inhibited by sputum samples from the COPD patients. The inhibition effect revealed by the microfluidic cell migration experiments provides new information about the complex involvement of T cell trafficking in COPD. Abstract : Inflammatory infiltration of leukocytes in the airway is associated with the pathogenesis of chronic obstructive pulmonary disease (COPD), but the mechanism of T cell migration involved in COPD remains poorly defined. This study used a microfluidic approach to assess the effect of COPD sputum on activated human peripheral blood T cell migration and chemotaxis under well‐controlled gradient conditions.